Effect of Posttreatment on the Catalytic Performances of Fe-N-C for Oxygen Reduction Reactions. (30th March 2023) - Kim, Dong-gun; Jang, Injoon; Sohn, Yeonsun; Joo, Eunhye; Jung, Chanil; Kim, Nam Dong; Jung, Jae Young; Paidi, Vinod K.; Lee, Kug-Seung; Kim, Pil; Yoo, Sung Jong
Abstract : Herein, we report the significance of posttreatment in the design of high-performance Fe-N-C-type catalysts for oxygen reduction reaction (ORR). Enhancing the catalytic performance of Fe-N-C requires a postprocess for removing the aggregated iron species formed during high-temperature pyrolysis since they have a negative effect on ORR. We were able to obtain a catalyst precursor for the Fe-N-C reaction via pyrolysis with iron-adsorbed 1, 8-diaminonaphthalene (FeDN), which was then treated with a concentrated HCl solution for the removal of the aggregated iron species produced. The HCl-treated FeDN was subsequently annealed at various temperatures to investigate the effect of the annealing process on the physical properties and ORR performance. The annealing temperature was a critical factor affecting the residual contents of impurities, as well as the active component and the electronic state of nitrogen. We also examined the influence of different types of acid (HCl, H2 SO4, and HNO3 ) on the catalytic performance. The type of acid used for removing aggregated iron species had an impact on both the Fe contents and the relative nitrogen species content. Among the catalysts tested, the catalyst prepared by annealing the HCl-treated FeDN at 700°C had the best ORR performance. Although its initial ORR performance in acidic conditions was lower than that of a commercial Pt/C, it was more durable. In alkaline conditions, it delivered a comparable initial ORR performance to Pt/C and also exhibited higher durability.